ANALYSING THE EFFECT OF THE ENGLISH PROFICIENCY TEST (EPT) WASHBACK ON ALGERIAN PHD CANDIDATES’ ACADEMIC WRITING PRACTICES - Djedda TAKOUACHET; Mohammed NAOUA (Analele Universităţii din Craiova. Psihologie, Pedagogie, 2025)
With English at the forefront of higher education, Algerian universities have integrated English proficiency requirements into its doctoral training programs. This is in consideration of the fact that English has become an essential medium for academic research, publication, and international scholarly communication. The present study, therefore, is an attempt to examine the washback effect of the English proficiency test on PhD candidates' academic writing practices; it analyzes how test requirements shape their learning strategies, development of their writing skill, and the engagement with English language learning. To conduct this analysis, a qualitative research design is adopted. The study draws on semi-structured interviews with 20 PhD candidates across Algerian universities to have a closer look on their test preparation strategies, challenges, and perceptions of the English proficiency test’s impact. The data was analyzed via thematic analysis. The results revealed both positive and negative washback effects on PhD candidates’ writing practices. In light of these findings, practical recommendations for aligning the English proficiency test more closely with PhD-level writing needs are presented.